Evaluation of the Effectiveness of Structured Teaching Programme on Knowledge regarding First Aid Management of Epilepsy among Primary School Teachers (Janaki Medical College Journal of Medical Science, 2023)
Background and Objectives Children and youth represent one of the fastly growing populations affected by epilepsy, which is the most common childhood neurologic condition. The clinical spectrum of children and youth with epilepsy (CYE) varies as some forms of epilepsy can have dramatic effects on brain development in early childhood and lead to poor functioning later in life. The aim of the study was to evaluate the effectiveness of structured teaching programme on knowledge regarding first aid management of epilepsy among primary school teachers.Materials and Methods: A pre-experimental one group pre-test and post-test design was used for the study.  A quantitative pre experiment method was used for this study. The sample consists of 60 primary school teachers of selected schools, Bangalore. They were chosen by a non-probability purposive sampling technique. A structured knowledge questionnaire was used to collect the data from the subjects. The obtained data was analyzed by using descriptive and inferential statistics and interpretation in terms of objectives and hypothesis of the study. The level of significance was set at 0.05 levels.Results: In the pre-test, majority of the respondents had inadequate knowledge with mean knowledge score of 43.2 % where as in post-test there was a significant gain in mean knowledge score of 85.3%. A significant association was found between demographic variables at 5% level of significance, the study shows there is the significant association of pre-test knowledge level with the demographic variables of respondents on Gender, marital status, Educational status, Know about first aid management of Epilepsy, teaching experience to an epileptic child, Experience in helping the epileptic child, ever observed student with epileptic attack in class room (P0.05) at 5% of significant level.Conclusion: The  finding of the study shows that in the pre-test, majority of the primary school teachers had inadequate knowledge regarding first aid management of epilepsy where as in post-test majority of teachers had gained adequate knowledge after administration of structured teaching programme. The structured teaching programme was effective in enhancing the knowledge regarding first aid management of epilepsy among primary school teachers working in selected schools, Bangalore.